Evaluating middle to late Holocene climate variability from δ18O of aquatic invertebrate remains in southwestern Greenland - Edgerton, Briana A.; Axford, Yarrow; Chipman, Melissa L. (Quaternary Science Reviews, 2024)
Holocene paleotemperature records from ice-free margins of Greenland suggest spatiotemporal heterogeneity in the timing of key climate transitions following retreat of the Greenland Ice Sheet. However, the paucity of high-resolution climate records from this region limits our understanding of the timing, spatial variation, and drivers of Holocene climate variability. Here, we present a middle to late Holocene climate reconstruction based on δ18O of aquatic invertebrate (chironomid and cladoceran) remains and sediment geochemistry from lake sediments to elucidate millennial to submillennial-scale drivers of climate in southwestern Greenland. We establish that our site, Arrowhead Lake, is a through-flowing basin with an integrated signal of annual meteoric water with no evidence of significant evaporative enrichment. Core sediment geochemistry captures the transition from minerogenic-dominated to organic-rich sediments ∼8 cal ka BP. Chitin-based δ18O measurements of both chironomid head capsules and ephippia exhibit similar temporal variability through the record, broadly decreasing from 8.2 cal ka BP to present, concurrent with decreasing summer insolation and regional Neoglacial cooling. A simplified assumption that temperature is the sole driver of changes in isotopes of precipitation yields an estimated average temperature change from the middle to late Holocene at Arrowhead Lake of 2.1–3.0 °C, comparable to existing estimates of middle to late Holocene temperature decline in western Greenland. Depleted δ18O values after 3.3 cal ka BP correspond to the onset of Neoglacial cooling and independent evidence for a slowdown of the West Greenland Current, and suggests that both temperature and sea-ice variability were important controls on isotopic variability at this site. Highly depleted isotopic values at 8.2 cal ka BP followed by high isotopic variability in the early part of the middle Holocene suggests that our record may capture regional 8.2 ka cooling. This new isotope record provides insight into climate influences during the middle and late Holocene along the western Greenland margin that are important for understanding how ongoing melt of the Greenland Ice Sheet and amplified warming in the Arctic may impact the climate system.
Keywords: Chitin; Greenland; Holocene; paleoclimatology; Stable isotopes; δO